anonymous
  • anonymous
I need some help on finding the solution, an ordered pair using the substitution method 3m + n = 1 m-5n = 11 can anyone help and explain I get so far and I am confused
Mathematics
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this
and thousands of other questions

anonymous
  • anonymous
The substitution method means you solve one equation for a variable and then plug that solution into the other equation for that variable.
anonymous
  • anonymous
so n = 1-3m m-5(1-3m) = 11 m-5+15m = 11 16m = 16 m=1. n = 1-3(1) = -2 n=-2
anonymous
  • anonymous
this is where i get confused

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
What are you confused on? Once you have your answers i.e m=1 and n=-2 you can write them as an ordered pair.
anonymous
  • anonymous
3m + n = 1 subtract 3m from both sides n=1-3m what r u confuzed about?
anonymous
  • anonymous
So (n,m) could be a pair or (m,n) depends on which one is independent and dependent.
anonymous
  • anonymous
why do you pick 3m, is there a reason on hwich one to pick
anonymous
  • anonymous
He is just solving for one of the variables if that is what you are asking. You want to get one of the variables in terms of the other so you will have an equation with only one unknown that you can solve for. He could have done 3m=1-n and then divided by 3 to solve for m and plug in into the other equation.
anonymous
  • anonymous
3m + n = 1 m - 5n = 11 3m - 3m + n = 1 - 3m
anonymous
  • anonymous
is that what i suppossed to do, then that equation would become n = 1-3m
anonymous
  • anonymous
That is how you would solve the first equation for n. Now you would replace n in the other equation with your "new" n=1-3m so m-5(1-3m)=11
anonymous
  • anonymous
m - 5(1-3m) = 11 this correct? then I would make it 5 - 16m = 11
anonymous
  • anonymous
The first part is correct, but the second part I believe you messed up on your signs. Should be -5+16m=11
anonymous
  • anonymous
Then how do I go next
anonymous
  • anonymous
Add 5 to both sides to get 16m=16 divide both sides by 16 to leave m=1
anonymous
  • anonymous
oh I thought I would have to subtract 5 from both sides not add, this is where I get confused on knowing which to do , add or subtract
anonymous
  • anonymous
Since the 5 is negative, you want to perform the opposite operation to get it on the other side. If the 5 was positive you would subtract it from both sides.
anonymous
  • anonymous
thank you this helps very much
anonymous
  • anonymous
You're welcome!

Looking for something else?

Not the answer you are looking for? Search for more explanations.